2005
DOI: 10.1097/01.mpa.0000161809.24284.33
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Cytokine Genes (TGF-??1, IFN-??, IL-6, IL-10, and TNF-??) in Patients With Chronic Pancreatitis

Abstract: The genotypes corresponding to the high TGF-beta1 producer phenotypes can be associated with the fibrogenesis shown with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
3
14
2
1
Order By: Relevance
“…In our study, the Il-6 genotypes frequency was similar in patients with pancreatic adenocarcinoma, chronic pancreatitis, and control group. The distribution found in healthy subjects was similar to that described in other Caucasian populations [15,20,24,32]. Other authors also did not find differences in the genotypic frequencies of the Il-6 gene between CP patient and healthy volunteers [24,32].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, the Il-6 genotypes frequency was similar in patients with pancreatic adenocarcinoma, chronic pancreatitis, and control group. The distribution found in healthy subjects was similar to that described in other Caucasian populations [15,20,24,32]. Other authors also did not find differences in the genotypic frequencies of the Il-6 gene between CP patient and healthy volunteers [24,32].…”
Section: Discussionsupporting
confidence: 83%
“…The distribution found in healthy subjects was similar to that described in other Caucasian populations [15,20,24,32]. Other authors also did not find differences in the genotypic frequencies of the Il-6 gene between CP patient and healthy volunteers [24,32]. In contrast, Landi et al reported that the allele C of Il-6 gene polymorphism at position -174 was associated with increased risk of colorectal cancer development [20].…”
Section: Discussionsupporting
confidence: 76%
“…IL-10 is an effective antifibrotic cytokine. Endogenous IL-10 may limit pancreatic gland atrophy and fibrosis as well as reduce the expression level of TGF-β 1 in pancreatic acinar cells and interstitial cells (Bendicho et al, 2005;Apte et al, 2007).…”
Section: Mensenchymal Stell Cells In Chronic Pancreatitismentioning
confidence: 99%
“…These genetic polymorphisms were shown to affect the overall expression and secretion of cytokines both in vitro and sporadically in vivo systems. Associations among polymorphisms in cytokine genes and inflammation, allograft rejection, autoimmune, and infectious diseases have been reported [4][5][6][7]. In diabetes mellitus, cytokine gene polymorphism may reflect or control the severity and progression of various immunological phenomena associated with the disease [8].…”
Section: Introductionmentioning
confidence: 99%